AB1003 Regain of Function in Patients with Juvenile Idiopathic Arthritis Lasts Longer than Reaching the State of Inactive Disease. (9th June 2015) - Hartmann, M.; Merker, J.; Kreuzpointner, F.; Rosenbaum, D.; Schwirtz, A.; Haas, J.-P.
Abstract : Background: In Juvenile idiopathic arthritis (JIA) accompanying pain leads to mal-positioning or compensatory movements [1], increasing the risk for osteoarthritis in long-lasting disease courses. In Germany about 1/3 of JIA patients (JIA-P) with polyarticular affection are treated with biologics [2]. This has led to substantial improvement according to disease activity [3]. Still there are hardly any objective analyses on the longitudinal development of functional effects of JIA on joint limitations, especially under treatment with biologics. Objectives: The aim of this work is to analyse the longitudinal effects of a combined treatment of JIA including anti-TNF-α therapy and functional therapies (e.g. physiotherapy) on walking abilities of JIA-P. Methods: In a prospective longitudinal study 37 polyarticular JIA-P were included and treated with an anti-TNF-α therapy plus regular physiotherapy. JIA-P performed a 3D- gait analysis (8 infrared cameras (Vicon), 2 ground reaction force (GRF) plates (AMTI)) including the Plug in Gait body model. The cohort diminished the size of participants because of lost to follow up (n=15), drop-out (n=1) and investigator-caused discontinuation (n=1). Finally 15 JIA-P (♀: 8; ♂: 7) were analysed according therapeutic effects at all three time-points: (i) before initial anti-TNF-α therapy (T0: 13.7±3.2yr; 1.58±0.17m; 49.8±18.6kg), (ii) after 3.7±0.7 months (T1) and (iii) after 9.9±2.9 months (T2). The results were compared to matched healthy controls (CG) (n=15, ♀=11; ♂=4; 13.5±4.1yr, 1.55±0.12m, 46.5±12.9kg). Because of multilevel affection in JIA-P, both legs of each participant were included. Additionally the Ped-ACR70 score was determined for 13 JIA-P. For statistics the one-way ANOVA with Dunnett Post-hoc test was used (p<0.05). Results: The results demonstrate that the gait function was significantly limited in the JIA-P at T0. JIA-P showed a reduced walking velocity, a not significant decreased hip range of motion (ROM), less power in the ankle at push-off and a reduced load in the vertical GRF (Fz ) in single support phase (Table 1 ). While the ankle power reached a normal size already in T1, the other parameters: walking velocity, hip ROM and Fz load reduction recovered much more slower, reaching values compatible to CG at T2. ACR70/remission were achieved by 62/62% at T1 and by 46/54% at T2. Limitation: 2 JIA-Ps had a relapse between T1 and T2. Conclusions: The results of the 3D gait analysis show that functional limitations in JIA-P with polyarticular affection are not completed even when patients under treatment already show good results according to remission criteria. These findings demonstrate the importance of functional therapies, as physiotherapy which should be continued after the regain of clinical inactivity precisely. References: Hartmann, M., et al. Int J Pediatr, 2010. Minden, K., et al. Z Rheumatol, 2013. 72(4): p. 339-46. Hashkes, P.J., et al. Nat Rev Rheumatol, 2010. 6(10): p. 561-71. Acknowledgements: The authors want to thank Pfizer Inc., the "Deutsche Kinderrheuma-Stiftung" and "Ironman-Hilfe Kinderrheuma" for supporting this study. Disclosure of Interest: None declared